ER-α36 prevents high glucose-induced cellular senescence and apoptosis in renal tubular cell - Dehai Yu; Ling Luo; Yu Liang; Huili Zhou; Yinghui Xiao; Xingna An; Yingzhao Wang; Zhonggao Xu; Weixia Sun; Wanning Wang (Frontiers in Endocrinology)
BackgroundThe estrogen-estrogen receptor (ER) system plays a significant role in the sexual dimorphism of diabetic kidney disease (DKD), yet its specific effects on renal tubular injury under diabetic conditions remain incompletely characterized.MethodsHuman renal tubular (HK-2) cells were exposed to high glucose (HG) to model diabetic conditions. Cell apoptosis was quantified by flow cytometry, and cell senescence was assessed via β-Gal staining. Western blotting was performed to analyze ER-α36 expression, PI3K/AKT pathway activity, apoptosis regulators (Bcl-2, Bax, cleaved caspase-3/7), and senescence markers (P53, P21, P27, P16). The regulatory effects of ER-α36 on EZH2 and PTEN were examined, and chromatin immunoprecipitation (ChIP) was used to assess H3K27me3 modifications at the PTEN promoter.ResultsHG treatment significantly induced apoptosis and senescence in HK-2 cells, concomitant with the suppression of PI3K/AKT signaling. These effects were associated with the downregulated EZH2 expression and reduced H3K27me3 enrichment at the PTEN promoter, leading to PTEN upregulation. ER-α36 overexpression partially restored PI3K/AKT signaling, attenuated cellular injury, and reversed HG-induced epigenetic changes at the PTEN locus.ConclusionsOur findings demonstrate that ER-α36 protects renal tubular cells from HG-induced damage through EZH2-mediated epigenetic regulation of PTEN and PI3K/AKT pathway activation. These results identify ER-α36 as a potential therapeutic target for DKD.